Respon Siswa Terhadap Media Augmented Reality Berbantuan Aplikasi Assembler dalam Pembelajaran Dongeng Bahasa Sunda - Erni Endah Sari; Temmy Widyastuti; Haris Santosa Nugraha; Hernawan Hernawan (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
The importance of educational technology as a learning medium that is more flexible, fun, can improve the cognitive process and skills of learners, so that it plays an active role in attracting students' interest or motivation to learn (Miasari et al., 2022). Many learning media utilize digital technology, one of which is augmented reality learning media assisted by assembler applications. The purpose of this study was to determine student responses to media products in learning Sundanese fairy tales at the elementary school level. The research design used descriptive qualitative with data collection techniques in the form of questionnaires and interviews given after the learning took place. Data analysis was carried out using a Likert scale. The results showed that students' responses to augmented reality media assisted by assembler applications in learning fairy tales with an average score percentage of 85.7% which was stated in the positive category. Thus, augmented reality learning media with the help of assembler applications obtained a positive response and succeeded in attracting students' attention in learning Sundanese fairy tales.